3D Printing Guide Implant Placement: A Case Report - Vlahović Zoran; Mikić Mirko (Balkan Stomatological Society, 2017)
Background: Cone Beam Computer Tomography (CBCT) is representing a new concept of radiological diagnostics and its application occupies a special place in implantology. Today, preoperative planning, and quantitative and qualitative jaw bone analysis cannot be done without the use of these techniques. The latest in a series of achievements in this field is a method of making a guide for implant using a 3D printing technique. This way pre implantology planning reduces the chance of surgical complications to a minimum and allows installation of dental implants in the most optimal position for future prosthetic work. Aim: To show benefits of guide implantation in clinical practice.